Extremal Numbers of Cycles Revisited. Issue 5 (28th May 2021) - Conlon, David
Abstract: We give a simple geometric interpretation of an algebraic construction of Wenger that gives n -vertex graphs with no cycle of length 4, 6, or 10 and close to the maximum number of edges.